RESEPSI HADIS DALAM FILM PENDEK “KAYA TAPI MISSQUEEN” CHANNEL YOUTUBE ISLAMIDOTCO - Hasan, Muhammad Ragil (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
This article discusses the reception of living hadith studies in the film "Kaya Tapi Missqueen" which was uploaded to the Islamidotco youtube channel. This film is a short film with a comedy nuance and tucked into Islamic teachings in the form of the Prophet’s hadith. The hadith reads: "The feet of a servant do not shift (towards the Shiratal Mustaqim limit) so that he is asked about his age for what he spends, his knowledge for what he does, his wealth from where he earns and where he spends it, and what he uses his body for." The hadith is because, it is to get how the reception of the living hadith in the film "Kaya Tapi Missqueen" looks like. The author does this by using the reception approach by Ahmad Rafiq who divides it into three reps. Namely, the reception of exageration, reception of esthetics, and reception of functional. The conclusions obtained in this article are 1) the reception of exagesis is formed in the presentation of the hadith as it is without adding a deeper meaning to the hadith; 2) the esthetic reception contained when Pardi (main character) gets a divine state when he dreams of being asked to account for his wealth by an angel in the grave; 3) the functional reception contained in the scene where Pardi is grateful and realizes that his property is only a deposit and will not be held accountable for the answer.